Probing the metallicity and ionization state of the circumgalactic medium at z~6 and beyond with OI absorption - Keating, Laura C.; Haehnelt, Martin G.; Becker, George D.; Bolton, James S. (Oxford University Press, 2013)
Low-ionization metal absorption due to O I has been identified as an important probe of the physical state of the intergalactic/circumgalactic medium at the tail end of reionization. We use here high-resolution hydrodynamic simulations to interpret the incidence rate of O I absorbers at z ∼ 6 as observed by Becker et al. We infer weak O I absorbers (EW ≳ 0.1 Å) to have typical H I column densities in the range of sub-damped Lyman α systems, densities of 80 times the mean baryonic density and metallicities of about 1/500th solar. This is similar to the metallicity inferred at similar overdensities at z ∼ 3, suggesting that the metal enrichment of the circumgalactic medium around low-mass galaxies has already progressed considerably by z ∼ 6. The apparently rapid evolution of the incidence rates for O I absorption over the redshift range 5 ≲ z ≲ 6 mirrors that of self-shielded Lyman-limit systems at lower redshift and is mainly due to the rapid decrease of the metagalactic photoionization rate at z ≳ 5. We predict the incidence rate of O I absorbers to continue to rise rapidly with increasing redshift as the IGM becomes more neutral. If the distribution of metals extends to lower density regions, O I absorbers will allow the metal enrichment of the increasingly neutral filamentary structures of the cosmic web to be probed.